Molecular biology of X-chromosome disease - Chen, Z; Chen, Zheng-Yi (1992)
﻿ Genomic clones were isolated and characterized using the human monoamine oxidase A (MAOA) cDNA to screen a phage library, constructed from a human 4X cell line (48, XXXX). The genomic contig derived from overlapping phage clones showed that the size of the MAOA gene is over 80 kb. Exon-containing fragments from these phage clones were subcloned and sequenced. The data from this showed that the MAOA gene consists of 15 exons. A YAC (yeast artificial chromosome) isolated using the MAOA cDNA was characterized. This YAC was found to contain both the MAOA and the MAOB genes. Using PFGE (pulsed-field gel electrophoresis) to investigate the YAC, it was found that the MAOA and the MAOB genes are located within 50 kb and adjacent to each other. The two genes are localized in a 3'-to-3' fashion, suggesting their expression may be regulated independently. The analysis of the homology shown by the two genes clearly demonstrated that they were derived from duplication of a common ancestral gene. A CpG island was discovered to be associated with the 5' end of both genes. A restriction map of -2.5 Mb of genomic DMA around the MAO genes was generated by PFGE. Long-range mapping defined the physical relationship between the marker L1.28 and the MAO genes as L1.28_MAOA_MAOB. A number of genetic diseases have been linked to the Xp11.3 region. Strong linkage was known to exist between the Norrie disease locus and L1.28. Studies showed that some of the Norrie patients have deletions encompassing the region which contains L1.28 as well as the MAO genes. Another YAC isolated by using L1.28 as the probe was also characterized. A phage library was constructed from the L1.28 YAC and the end clones were isolated. Studies on some of the Norrie deletion patients showed that the proximal end clone of the YAC was retained in one of the deletion patients. Previous studies had shown that the Norrie disease locus was also localized proximal to the 5' end of the MAOB gene. The combined information placed the disease locus to an interval of 240 kb within the YAC. More phage clones were characterized in order to define further the region for the Norrie locus which was finally localized within 160 kb. A YAC fragment of 160 kb was isolated and used to screen two human retinal cDNA libraries. Among the cDNAs isolated, one group was found to be deleted in some of the Norrie patients previously without any known deletion, which established their candidacy as the transcripts of the Norrie disease locus. Further characterization of the candidate gene showed that it is conserved across species. The expression of the gene was detected in various tissues. The homology shared between the NDP gene and some of the growth factor binding proteins suggests its role in neural cell proliferation and differentiation.